Development of an item bank for measuring prosthetic mobility in people with lower limb amputation: The Prosthetic Limb Users Survey of Mobility (PLUS‐M). Issue 4 (31st March 2023) - Hafner, Brian J.; Amtmann, Dagmar; Morgan, Sara J.; Abrahamson, Daniel C.; Askew, Robert L.; Bamer, Alyssa M.; Salem, Rana; Gaunaurd, Ignacio A.; Gailey, Robert S.; Czerniecki, Joseph M.; Fatone, Stefania; et al.
Abstract: Background: Achieving mobility with a prosthesis is a common post‐amputation rehabilitation goal and primary outcome in prosthetic research studies. Patient‐reported outcome measures (PROMs) available to measure prosthetic mobility have practical and psychometric limitations that inhibit their use in clinical care and research. Objective: To develop a brief, clinically meaningful, and psychometrically robust PROM to measure prosthetic mobility. Design: A cross‐sectional study was conducted to administer previously developed candidate items to a national sample of lower limb prosthesis users. Items were calibrated to an item response theory model and two fixed‐length short forms were created. Instruments were assessed for readability, effective range of measurement, agreement with the full item bank, ceiling and floor effects, convergent validity, and known groups validity. Setting: Participants were recruited using flyers posted in hospitals and prosthetics clinics across the United States, magazine advertisements, notices posted to consumer websites, and direct mailings. Participants: Adult prosthesis users (N = 1091) with unilateral lower limb amputation due to traumatic or dysvascular causes. Interventions: Not applicable. Main Outcome Measures: Candidate items (N = 105) were administered along with the Patient Reported Outcome Measurement Information System Brief Profile, Prosthesis Evaluation Questionnaire – Mobility Subscale, and Activities‐Specific Balance Confidence Scale, and questions created to characterize respondents. Results: A bank of 44 calibrated self‐report items, termed the Prosthetic Limb Users Survey of Mobility (PLUS‐M), was produced. Clinical and statistical criteria were used to select items for 7‐ and 12‐item short forms. PLUS‐M instruments had an 8th grade reading level, measured with precision across a wide range of respondents, exhibited little‐to‐no ceiling or floor effects, correlated expectedly with scores from existing PROMs, and differentiated between groups of respondents expected to have different levels of mobility. Conclusion: The PLUS‐M appears to be well suited to measuring prosthetic mobility in people with lower limb amputation. PLUS‐M instruments are recommended for use in clinical and research settings.